Challenges and Opportunities in the Implementation of Inclusive Education in Latin America: A Comprehensive Analysis with a Focus on Ecuador - Arteaga-Alcívar, Yamileth; Guaña-Moya, Javier; Pontón, Raúl Guillermo Zambrano; Cajamarca-Carrazco, Diego; Arequipa, Edwin Edison Quinatoa (Journal of Posthumanism, 2025)
This study analyzes the challenges and opportunities in the implementation of inclusive education in Latin America, with a particular focus on Ecuador. Through a regional comparative analysis and a multiple case study in Ecuador, the policies, practices and perceptions of various educational actors were examined. The results reveal significant variability in implementation between countries, with Chile and Colombia leading in inclusion rates. In Ecuador, persistent challenges were identified, mainly in teacher training, inadequate resources and curricular adaptation. The perceptions of educational actors vary, with principals showing higher understanding than teachers. Inclusive practices in the classroom are inconsistent, although collaborative work is frequent. A positive correlation was found between high levels of implementation of inclusive practices and better academic performance, lower dropouts, and higher student satisfaction. Factors such as committed leadership and ongoing staff training were identified as crucial to success. The study concludes that, despite advances in legal frameworks and policies, a significant gap persists between theory and practice, underscoring the need for a more comprehensive and sustained approach to the implementation of inclusive education.